Design and Construction of an Automated Flood Intimation System - Rezwan Us Saleheen; Ahmed Farhan; Enamul Hoq; Farhan Mahbub (MultiTech Publisher, 2023)
Flooding is a crucial concern for creating substantial economic and social impacts for different regions of Bangladesh. The country's geographical location makes most of the area highly vulnerable to floods. Despite people's suffering during flood conditions, comprehensive research on developing an automotive flood intimation system is inadequate. Flooding is the inundation of water onto land that is normally dry, followed by rain, snow, coastal storms, storm surges, overflows of rivers, and dam failure. Early detection of rising water levels may reduce the damaging impact of floods and also allow adequate time to develop integrated flood adaptation and management mechanisms. Therefore, this study proposed an automated flood intimation system using Arduino. The system integrates the feature of determining three distinct parameters involving temperature, humidity, water level, and wind speed. The design emphasized the early detection of rising water levels and provided the necessary acknowledgement to reduce the impact of floods. Post-flood effects involve water pollution, water-borne diseases, and other epidemics in flood-affected communities. Hence, the proposed system might be helpful for proper support management during natural calamities like floods to reduce the suffering of people.